On some topological properties for special Classes of banach spaces. Part 2 - Kasyanov, P.; Mel'nik, V. (Навчально-науковий комплекс "Інститут прикладного системного аналізу" НТУУ "КПІ" МОН та НАН України, 2008)
We consider some classes of infinite-dimensional Banach spaces with integrable derivatives. A compactness lemma for nonreflexive spaces is obtained. However some main topological properties for the given spaces are obtained.